Covid19 Disaster: Examining the Role of the Village Head in Settlement of Civil Cases - Muhammad Naufal Ramli; Pregnon Claude Nahi; Rizki Ramadani (Manunggal Halim Jaya, 2022)
This study aims to determine the authority and role of the village head in resolving civil cases currently being faced during the Covid-19 pandemic. This study uses a normative juridical research method. The results of this study indicate that the Village Head has the authority to lead the administration of village governance, establish village regulations, foster village community life, and foster peace and order in the village community. Then the authority of the Village Head One way to resolve civil dispute cases is by facilitating, mediating, and coaching as well as motivating the public to resolve disputes between the two parties. The role of the Village Head in resolving civil dispute cases is as a peace judge before entering the realm of litigation. It was found that the role is the same as that of judges in the realm of litigation, in that the village head becomes a facilitator in civil matters or cases, plays a passive role but is oriented towards mitigating more widespread conflicts within his territory. The COVID-19 pandemic has reduced the resolution of disputes into the realm of litigation, but many have been resolved by village heads as an anticipatory measure against the spread of the virus. The results of this study recommend that the role of the village head can carry out the function of a judge in resolving civil issues through training organized by relevant institutions for the settlement of civil cases.